A real‐world study of alemtuzumab in a cohort of Italian patients. (5th October 2021) - Russo, Cinzia Valeria; Saccà, Francesco; Frau, Jessica; Annovazzi, Pietro; Signoriello, Elisabetta; Bonavita, Simona; Grasso, Roberta; Clerico, Marinella; Cordioli, Cinzia; Laroni, Alice; Capobianco, Marco; Torri Clerici, Valentina; et al.
Abstract: Background and purpose: Real‐world data on alemtuzumab are limited and do not provide evidence of its effectiveness after various disease‐modifying therapies (DMTs). Our aim was to provide real‐world data on the impact of clinical variables and previous DMTs on clinical response to alemtuzumab. Methods: Sixteen Italian multiple sclerosis centers retrospectively included patients who started alemtuzumab from January 2015 to December 2018, and recorded demographics, previous therapies, washout duration, relapses, Expanded Disability Status Scale (EDSS) score, and magnetic resonance imaging data. Negative binomial regression models were used to assess the effect of factors on annualized relapse (ARR) after alemtuzumab initiation. Results: We studied 322 patients (mean age 36.8 years, median EDSS score 3, median follow‐up 1.94 years). Previous treatments were: fingolimod (106), natalizumab (80), first‐line oral agents (56), first‐line injectables (interferon/glatiramer acetate; 30), and other drugs (15). Thirty‐five patients were treatment‐naïve. The pre‐alemtuzumab ARR was 0.99 and decreased to 0.13 during alemtuzumab treatment ( p  < 0.001). The number of previous‐year relapses was associated with alemtuzumab ARR (adjusted risk ratio [RR] 1.38, p  = 0.009). Progression‐free survival was 94.5% after 1 year, and 89.2% after 2 years of alemtuzumab treatment. EDSS score improvement occurred in 13.5% after 1 year, and 20.6% after 2 years. Re‐baselining patients after 6 months of alemtuzumab treatment, led to no evidence of disease activity status in 71.6% after 1 year and 58.9% after 2 years. Conclusions: Alemtuzumab decreases ARR independent of previous therapy, including patients with disease activity during natalizumab treatment. Overall, 90% of patients showed no disease progression, and 20% an improvement after 2 years of alemtuzumab. Abstract : Alemtuzumab decreases annualized relapse independent of previous therapy, including in patients with disease activity during natalizumab treatment. Overall, 90% of patients show no disease progression, and 20% an improvement after 2 years of alemtuzumab. Re‐baselining patients after 6 months, led to no evidence of disease activity status in 71.6% after 1 year and 58.9% after 2 years.